MULTIMEDIA RESOURCES FOR EDUCATION - Conceição, William; Morandini, Marcelo (Seven Editora, 2025)
This work analyzes the relevance of Storytelling and Podcast as multimedia resources in contemporary education, highlighting their importance for promoting engagement and interaction between educators and students. In light of sociocultural theories, especially Vygotsky's concept of Zone of Proximal Development (ZPD), the research emphasized how personalized narratives can facilitate the construction of knowledge by connecting academic content with students' real experiences, arousing their interest and making learning easier. most significant for your personal and professional development. Furthermore, the study highlighted the need for ongoing training for educators in order to effectively integrate these approaches into their teaching practices. The proposed guidelines aim to encourage teaching that values creativity, collaboration and empathy, preparing students for the challenges of the 21st century. In short, implementing narrative and multimedia-based strategies not only enriches the learning experience, but also contributes to a more inclusive and adaptable education to the demands of today's society.DOI: https://doi.org/10.56238/sevened2025.038-004